Micropatterning of Nonplanar Surfaces on 3D Devices Using Conformal Template Vacuum Bagging. Issue 5 (27th February 2018) - Alaie, Seyedhamidreza; Robinson, Sanlin S.; Amiri Moghadam, Amir Ali; Auge, Jordyn; Datye, Amit; Sidoti, Hannah; Doshi, Tejas; Gharaie, Saleh Hassanzadeh; Min, James K.; Mosadegh, Bobak; Dunham, Simon
Abstract: Micropatterning provides a powerful means for engineering surface properties, such as friction, adhesion, and biocompatibility, with promise for medical device applications. While soft lithography allows for micropatterning on curved surfaces, there are limitations to the level of curvature and object complexity achievable. A cost effective and simple method is realized for micropatterning complex 3D objects and is demonstrated for a variety of micropatterns, materials, and devices. The technique integrates the simple principles of soft lithography for fabrication of flexible templates, and vacuum bagging, for transfer of the patterns on arbitrary shaped nonplanar objects. The technique is demonstrated with silicones, polyurethanes, and nitinol materials ubiquitous in medical devices, due to their mechanics, biocompatibility, and hemocompatibility. Micropatterns inspired by shark skin riblets and tree frogs are demonstrated. The flexibility of this method is demonstrated by transferring patterns to various objects/devices, including 3D printed objects, soft robotic grippers, guidewires, and balloon catheters. Abstract : A cost effective and simple method is realized for micropatterning complex 3D objects with medical applications. It is demonstrated for a variety of micropatterns (inspired by tree frogs and shark skin), materials (medical grade polyurethanes), and devices (nitinol guidewires, balloon catheters, and soft grippers). The technique is ideal for rapid prototyping of medical devices.